Treatment by the Law and Society of Parents of Minors Who Have Died in Circumstances Where They Were Denied Medical Intervention - Worley, Heather (Auckland University of Technology, 2003)
Between 1999 and 2001, three children belonging to three sets of parents developed illnesses which were to prove fatal. In each of the cases the parents chose non-orthodox treatment ahead of medical treatment and the law and society responded very differently to each of the three cases. In one case all orders against the parents were dropped for the paramountcy of their child’s welfare, in the second case the parents received convictions with suspended sentences and in the third case the parents received prison sentences for manslaughter. The purpose of the research is to identify and highlight inconsistencies which occurred not only in the courts, but also with general public reaction and to examine possible reasons for the different legal penalties inflicted on the parents. It is also important to illustrate differing attitudes of some members of society towards alternative versus conventional medicine and also to intense religious beliefs. The research asks a number of questions concerning the paramountcy of children’s right to life, self-determination and the court’s role in these circumstances. Critical legal theory is used, exploring case law and legislation internationally and within New Zealand. From this a framework is established which consists of investigating the historical relationship between medicine and the law and best interests as it relates to the cases in the research. The rights of children as autonomous individuals are seen to be of major importance in medical decision-making. The legal positions for people who refuse consent to treatment either on their own behalf or on the behalf of minors are also examined, including the rights of parents who refuse consent to medical treatment on religious grounds. There is a brief discussion concerning accountability for alternative health therapy practitioners. It is found that although the Code of Health and Disability Services Consumers’ Rights 1996 offers the presumption of capacity to consent to treatment without age providing an artificial barrier, the legal position of a minor to refuse consent to treatment is unclear. The law and society appear reluctant to allow a child to be placed at risk of death or harm because of religious beliefs. Possibly this is due to the value the State places on the sanctity of life, which sometimes overrides the right to practice religion without interference. Finally, there is a discussion about New Zealand’s progress with guidelines which have been suggested by national and international organisations regarding improving situations for families who find themselves in similar circumstances and for at-risk children in general. It is seen that New Zealand has been slow to implement recommended proposals. The exploratory nature of this research serves to highlight certain inconsistencies and areas of concern involving children and their families, in the hospital setting and in a court situation. These concerns could warrant further investigation within both the health and legal professions, which is beyond the scope of the current discussion.
Keywords: Health -- Law and legislation -- New Zealand; Parent and child (Law) -- New Zealand; Alternative medicine; Complementary Therapies; Children -- Legal status, laws, etc -- New Zealand